Relação entre poluição do ar e internações de idosos por doenças isquêmicas do coração em São Paulo entre 2000 e 2012. - Melo, Marta Lígia Vieira (2015)
Introduction: Air pollution in industrialized urban centers triggers numerous compromises on human health and its effects are associated with the increase in demand for health services. Objective: This study was designed to investigate the relationship between exposure to air pollution and elderly hospitalizations in the Sistema Único de Saúde (SUS) due to ischaemic heart disease (IHD) in São Paulo city, from 2000 to 2012, stratified by sex. Method: This is an ecological time series study. Daily records of PM10, CO, SO2, NO2, O3, minimum temperature and humidity average were obtained from the São Paulo State Environmental Company. Hospital admissions were obtained from SUS database (DATASUS). Generalized linear polynomial distributed lag model was used to assess the effect of pollutants on the outcome. The level of significance of 5%. Results: In São Paulo, all primary pollutants were associated with the outcome (acute and one day-lag). For instance, an interquartile range increase in PM10 (24.42 ¿g/m3) was associated with a 2.50% (95% CI: 1.56%-3.44%) in total, 2.89% (CI95%: 1.43%-4.35%) for men and a 3.31% (95% CI: 1.65%-4.98%) for women, in the same day of exposure. The effects of SO2 was observed in the same day and one lag day. An interquartile range increase of 7.48 ¿g/m3 was observed increase of 4.02% (IC 95%:3.09%¿4.95%) in total, 5,61% (95%CI: 4.16%-7.06%) for men and a 3.79% (CI95%: 2.13%-5.45%) for women, in the same day. An interquartile range increase in NO2 (51.89 ¿g/m3) was observed increase of 3.47% (95%CI: 2.57%-4.36%) in total, 4.52% (95%CI: 3.13%-5.92%) for men and 4.44% (95%CI: 2.87%-6.02%) for women, in the same day. For CO, an interquartile range increase (1.33ppm) was associated with a 1.35% (95%CI: 0.50%-2.21%) in total, 1,94% (95%CI: 0.62%-3.26%) for men and 1.84% (95%CI: 0.34%-3.34%) for women. Conclusion: Elevation in air pollutants were associated with increased risk of IHD. Proper environmental policy will be necessary to limit the impact of air pollution on IHD on the vulnerable population.